The Interaction Test of Binary Mixtures of Endocrine-Disrupting Chemicals Using In Vitro Bioassays. (22nd June 2020) - Tang, Qianqian; Lei, Bingli; Liu, Yun; Zhang, Xiaolan; Liu, Qian; Sun, Su
Abstract : Typical environmental endocrine-disrupting chemicals (EDCs) such as estradiol valerate (EV), diethylstilbestrol (DES), di-2-ethylhexyl phthalate (DEHP), mono-2-ethylhexyl phthalate (MEHP), and bisphenol A (BPA) have a strong reproductive and developmental toxicity at low concentrations. However, information on their joint toxicity is scarce. In this study, we evaluated the combined effects of EV and other four EDCs (DES, DEHP, MEHP, and BPA) on the human breast MCF-7 cells by detecting the cell proliferation, intracellular reactive oxygen species (ROS) levels, and estrogen receptor alpha (ER α ) protein expression using equal concentration ratio method. The results showed that, after exposure for 24, 48, and 72 h, single EV, DES, and BPA can promote the proliferation of MCF-7 human breast cancer cells, and EV has the strongest effect in inducing cell proliferation. DEHP and MEHP cannot induce MCF-7 cell proliferation for all exposure time, while cell proliferation induced by EV was significantly attenuated by DES, BPA, DEHP, and MEHP when they mixed with EV. For intracellular ROS, single EV, BPA, DES, DEHP, and MEHP elevated intracellular ROS levels for different exposure time. Similar to the cell proliferation, DES and BPA decreased intracellular ROS levels induced by EV when they mixed with EV for 24 h. EV, DES, and BPA exposed alone or combined with EV upregulated the ER α protein expression. However, DEHP and MEHP exposed alone or combined with EV had no effect on ER α protein expression, indicating that DEHP or MEHP could attenuate ER α protein expression upregulated by EV. These results showed that the joint toxicity of binary mixtures of EV and other EDCs do not interact in a synergistic fashion in inducing cell proliferation, intracellular ROS levels, and ER α protein expression. These findings have important implications in the human risk assessments of EV mixed with other EDCs in the environment.